Analisis Pendapatan PDRB di Kota Batam Pada Tahun 2017-2020 - Shinta Dewi; Angeline Aurellia; Jeslin Jeslin; Kristina Kristina; Sherry Sherry (POINT: Jurnal Ekonomi dan Manajemen, 2021)
This study aims to determine the GRDP in Batam City. The secondary data used is time-series data taken in 2017-2020. This research method uses qualitative analysis, a data collection technique that uses library research by finding and reading references from various sources. The results show that the Indonesian economy has increased from year to year until 2020 where there was a COVID-19 outbreak, henceforth significantly declining the GRDP of Batam from 5.92% to -2.55%. Various sectors experienced a massive downswing in economic growth, one of which was the provision of accommodation and food and beverage with a figure of -45.49%. In conclusion, both the GRDP and APBD experienced a significant decrease in the city of Batam in 2020. As a consideration, the Indonesian government could restore the economy of Batam by empowering qualified human resources, encouraging household consumption, and foreign investment into Batam.